Characterization of Helicobacter pylori adhesin thiol peroxidase (HP0390) purified from Escherichia coli - Nguyen, Huyen Thi Minh; Nam, Kwang-Ho; Saleem, Yasar; Kim, Key-Sun (INDIAN ACAD SCIENCES, 2010)
The antioxidant protein, adhesin thiol peroxidase (HpTpx or HP0390), plays an important role in enabling Helicobacter pylori to survive gastric oxidative stress. The bacterium colonizes the host stomach and produces gastric cancer. However, little information is available about the biochemical characteristics of HpTpx. We expressed recombinant HpTpx in Escherichia coli, purified to homogeneity, and characterized it. The results showed that HpTpx existed in a monomeric hydrodynamic form and the enzyme fully retained its peroxidase and antioxidant activities. The catalytic reaction of the enzyme was similar to an atypical 2-cysteine peroxiredoxin (Prx). The conformation of the enzyme was observed in the presence and absence of dithiothreitol (DTT); similar to other known thiol peroxidases, conformational change was observed in HpTpx by the addition of DTT.